PENGARUH PENDIDIKAN KARAKTER DI RUMAH TANGGA TERHADAP KEMAMPUAN ETIKA BERKOMUNIKASI REMAJA DI ERA DIGITAL JORONG KOTO BARU SARIAK LAWEH KEC. AKABILURU KAB. LIMA PULUH KOTA - Hana Wahyuni; Erni Kasmawati; Deswalantri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education can be instilled in various environments, one of which is within the household. Character education in the family is realized through the education and teaching provided by parents to their children, particularly regarding manners, good morals, and the ethics of speaking and communicating in everyday life. This is especially important in the digital age, where almost all aspects of life have been maximized through technology. The development of digital technology has had a negative impact, especially among teenagers, as seen in the large number of teenagers who are still uncivilized in speaking to older people, are rude in their communication, and use coarse and inappropriate language in their daily lives. In addition, teenagers are also often unwise in uploading content and posting comments on social media. Many inappropriate slang terms are absorbed from social media, such as anjay, anjir, asu (dog), bangsat, kapret, and bacot, which are then carried over into everyday communication and social media. This study aims to determine the influence and extent of character education in households on the ethical communication skills of adolescents in the digital age in Jorong Koto Baru Sariak Laweh, Akabiluru District, Lima Puluh Kota Regency. The method used is quantitative correlational with data collection techniques in the form of questionnaire distribution and documentation. The population and sample consisted of 78 respondents. Data analysis techniques included correlation analysis, simple linear regression, t-test, and determination test (R²). The results of the analysis showed a regression equation of Y = 38.272 + 0.494X with a coefficient of determination of 0.142. This means that character education in the household has a positive effect on the ethical communication of adolescents by 14.2%, although the contribution is relatively weak but significant.